1990
DOI: 10.1007/bf00023376
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of brown seaweeds in an outdoor cultivation system and their cytokinin-like activity

Abstract: Four of the most abundant intertidal eastern Mediterranean brown seaweeds were repeatedly inoculated in an outdoor cultivation system for acclimatization. Dictyopteris membranacea was best acclimated and survived for nine months in the system. D. membranacea growth rate showed a positive relationship with irradiance and temperature during nine months of cultivation. Cystoseira sp., Sargassum vulgare and Padina pavonia were not acclimated and survived for shorter times, presumably because of inadequate conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Other OA have also proved effective when utilised in seed priming. Improved germination rates were seen in radish after seeds were treated with seaweed extract (Friedlander and Ben-Amotz 1990), and enhanced root elongation in germinating maize was noted by Eyheraguibel et al (2008) who used humic substances as a seed treatment.…”
Section: Organic Amendments Applied To Stimulate Plant Growthmentioning
confidence: 95%
“…Other OA have also proved effective when utilised in seed priming. Improved germination rates were seen in radish after seeds were treated with seaweed extract (Friedlander and Ben-Amotz 1990), and enhanced root elongation in germinating maize was noted by Eyheraguibel et al (2008) who used humic substances as a seed treatment.…”
Section: Organic Amendments Applied To Stimulate Plant Growthmentioning
confidence: 95%
“…MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content. 2 cytokinin, gibberellin, and abscisic acid are mostly present, along with additional active ingredients such sugar alcohol, betaine, seaweed polysaccharide, and phenolic compounds [10,11], which have been used in agriculture for many years [12,13]. The enhanced growth-promoting action of seaweed extracts on plants can be attributed to a combination of active compounds that act either directly or by modulating gene expression in the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed extracts (SEs) are a kind of biostimulant extracted from seaweed (especially brown algae) that can promote crop growth, improve crop quality, and enhance crop stress resistance. SE mainly contain natural hormones, such as auxin, cytokinin, gibberellin, abscisic acid, and other active substances such as seaweed polysaccharide, sugar alcohol, betaine, and phenolic compounds ( Crouch and van Staden, 1993 ; Jardin, 2012 ; Battacharyya et al, 2015 ), which have been used in agriculture for many years ( Friedlander and Ben-Amotz, 1990 ; Mukherjee and Patel, 2020 ). The studies have shown that SEs were beneficial to soil improvement and crop growth.…”
Section: Introductionmentioning
confidence: 99%